2021
DOI: 10.7153/fdc-2021-11-11
|View full text |Cite
|
Sign up to set email alerts
|

On the analysis of Black-Scholes equation for European call option involving a fractional order with generalized two dimensional differential transform method

Abstract: This paper proposes alternative approach for the valuation of a European call option via Generalized Two Dimensional Differential Transform Method (GTDTM). The analysis of the Black-Scholes equation for a European call option involving fractional order with GTDTM is discussed. The fractional derivative is considered in the sense of Caputo. Also, it is assumed that the underlying asset price pays no dividend and follows the Geometric Brownian Motion (GBM). The fractional Black-Scholes equation for a European ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The versatile nature of fractional-order calculus allows for a nuanced and more accurate representation of complex systems [8,9], fostering advancements in interdisciplinary research [10] and practical problem-solving. Kelly et al [11] demonstrated that the Fractional Advection-Dispersion equation's space-fractional model is mathematically equivalent to the corresponding time-fractional model.…”
Section: Fractional Order Applications In Multi-disciplinary Fieldsmentioning
confidence: 99%
“…The versatile nature of fractional-order calculus allows for a nuanced and more accurate representation of complex systems [8,9], fostering advancements in interdisciplinary research [10] and practical problem-solving. Kelly et al [11] demonstrated that the Fractional Advection-Dispersion equation's space-fractional model is mathematically equivalent to the corresponding time-fractional model.…”
Section: Fractional Order Applications In Multi-disciplinary Fieldsmentioning
confidence: 99%